A study on compressive strength of concrete cointaining MK7003 with various water binder ratio / Clotilda Petrus … [et al.] - Clotilda, Petrus; Yusuff, Amer; Othman, Ahmad Fairuz; Mohd Zin, Ahmad Ikhwan Naim (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
The study was conducted to determine the effects of using MK7003 as a partial replacement material for OPC on the compressive strength of concrete. The study was further enhanced by studying the effects of varying the water binder ratio. Replacement level of 5%, 10% and 15% by weight of OPC in the control concrete were considered while maintaining water binder ratio at 0.47. Another study was conducted by varying the water binder ratios of 0.35, 0.45 and 0.55 while maintaining MK7003 content at 10% by weight. From the study it was found that increasing the level of MK7003 has a significant increase in the compressive strength of concrete but as the water binder ratio is increased the compressive strength of concrete will decrease.